2-Pyridyl substituents enhance the activity of palladium–phospha-adamantane catalysts for the methoxycarbonylation of phenylacetylene. Issue 1 (6th December 2016) - Shuttleworth, Timothy A.; Miles-Hobbs, Alexandra M.; Pringle, Paul G.; Sparkes, Hazel A.
Abstract : The pyridyl-N in Pt and Pd complexes of CgP(2-py) can be protonated or can coordinate to form a P, N-chelate; these features are linked with the carbonylation catalysis results. Abstract : The synthesis of a series of CgPAr ligands is reported, where CgP is the 6-phospha-2, 4, 8-trioxa-1, 3, 5, 7-tetramethyladamant-6-yl moiety and Ar = 2-pyridyl (L2 ), 3-pyridyl (L3 ), 2-pyrimidyl (L4 ), 4-R-2-pyridyl [R = Me (L5a ), CF3 (L6a ), SiMe3 (L7a )] or 6-R-2-pyridyl [R = Me (L5b ), CF3 (L6b ), SiMe3 (L7b ). Testing of these ligands in the Pd-catalysed methoxycarbonylation of phenylacetylene reveals that the activity and branched selectivity of the catalysts derived from these ligands varies as a function of the N-heterocycle, with the catalyst derived fromL5b being the most active of those tested. This, together with the poor performance of catalysts derived fromL3 supports the hypothesis that the catalysis proceeds by a "proton shuttling" mechanism, an idea that previously had only been applied to arylphosphines. Reaction of [PtCl2 (cod)] with L where L =L2 orL4–7 yields a rac / meso mixture of the trans -[PtCl2 (L)2 ] (1a–h ) complexes, three of which are structurally characterised. 31 P NMR spectroscopy shows that reaction ofL3 with [PtCl2 (cod)] gives a mixture of mononuclear and binuclear metal complexes in solution. The complex trans -[PdCl2 (L2 )2 ] (4 ) reacts with AgBF4 to give the [PdCl(κ 1 -L2 )(κ 2 -L2 )]BF4 (5 ) with spectroscopic and structural characterisation confirming the presence of a P, N-chelate. 1 H and 31 P NMR evidence supports the assignment of a pyridyl-protonated species being formed upon treatment of4 with TsOH·H2 O in CD2 Cl2 ; both the protonated species and chelate5 are observed when the reaction is carried out in MeOH.